Prognosis of Down's syndrome with acute leukaemia. Issue 2 (February 1990) - Levitt, G A; Stiller, C A; Chessells, J M
Abstract : The outcome in children with acute leukaemia with (n = 90) and without Down's syndrome (n = 4377) was compared. Sixty three (70%) of those with Down's syndrome had acute lymphoblastic leukaemia and in comparison with 3664 (84%) controls had similar prognostic features except for a significant excess of the 'common' immunological subtype of acute lymphoblastic leukaemia. The outcome of the children with Down's syndrome was significantly worse with a five year overall actuarial survival of 28% compared with 59% in the control group. It appeared that both suboptimal chemotherapy and a high rate of infective problems contributed to the poor survival. Twenty six children with Down's syndrome had acute myeloblastic leukaemia and were significantly younger and had a higher percentage of the megakaryocytic and erythroid subtypes of acute myeloblastic leukaemia than the 713 controls. The outcome was similar in the two groups. It is concluded that the patients with Down's syndrome who develop acute leukaemia should receive standard protocols without modification, but aggressive supportive care is necessary to improve outcome.